Business Cycles, Effective Working Capital Management and Corporate Profitability - Enqvist, Julius (My University, 2010)
The current economic downturn has been characterized by liquidity shortages, increased bankruptcies and demand fluctuations. Companies world wide are seeking to increase efficiency, which after many prosperous years, has restored focus on working capital management. In Finnish listed companies between 1990 and 2008 working capital accounted for a fifth of the companies’ total assets. The way in which these substantial assets are managed is expected to have an effect on overall profitability. Due to increased focus on working capital by corporations the purpose of this thesis is to study the relationship between efficient working capital management and corporate profitability. Furthermore the thesis analyzes the role that the state of the business cycle plays in the working capital – profitability relationship. The efficiency of working capital is measured by the cash conversion cycle (CCC), which is the time lag between the purchase of materials during the production phase and receiving payment for the produced goods upon sale. The longer this time gap is the more working capital a company needs to finance its operations during this period. The CCC is made up of three components; accounts payable, accounts receivable and inventories. Through independently optimizing each individual component companies can achieve overall working capital efficiency. Regression analyses between the CCC, its individual components and profitability are conducted on a sample of Finnish listed companies between 1990 and 2008. Results show that firms can enhance profitability by increasing working capital efficiency. A negative relationship between the CCC, each of its components and profitability is found. Moderate evidence is found to support the notion that working capital management is more important in poor states of the economy, and very limited evidence is found to suggest that the significance of working capital management decreases in economic booms. Results suggest that working capital management should be included in firm’s financial planning.
Keywords: working capital; business cycles; profitability; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|